Simulation-based separation of mixed material joints using X-ray computed tomography - Busch, Matthias; Binder, Felix; Hausotte, Tino (ICCSE2 - 2nd International Conference on Computations for Science and Engineering, 2022)
X-ray computed tomography (XCT) is a fast-growing and non-destructive measurement technology for industrial applications. However, measuring assemblies with XCT consisting of several materials is challenging due to beam hardening or metal artifacts. The distinction between closely spaced surfaces, as in commonly used mixed materials joints like clinched connections or rivets, may even become inconclusive and limits the dimensional measurability. An improving approach to distinguish such surfaces is to use an energy-sensitive detector optimized for the specific material combination. For such an optimization a suitable spectral sensitivity has to be determined first. Therefore, a study is conducted with a simulated clinched connection probe joining two sheets of aluminum and steel and using the surface deviation error for further evaluation. The resulting spectral sensitivity curves may be used to further improve the separation of mixed material joints with dimensional XCT measurement